Oxidative stress markers cannot be used as endometriosis biomarkers in infertile patients - Vid Janša; Joško Osredkar; Ivan Verdenik; Tea Lanišnik Rižner; Helena Ban Frangež (Taylor & Francis Group, 2023)
Objectives Endometriosis is a common benign gynaecological disease that significantly compromises the quality of life of patients. To date, invasive surgery is the method of choice to visually and histologically confirm endometriosis. Thus, there is a major interest to develop noninvasive diagnostic tools. Oxidative stress is one of the proposed mechanisms of pathogenesis and may be involved in pelvic pain, dysmenorrhea, dyspareunia, and infertility in endometriosis patients. Thus, markers of oxidative stress may serve as diagnostic biomarkers for endometriosis.Design This prospective case-control study assessed erythrocyte superoxide dismutase (SOD), erythrocyte glutathione peroxidase (GPX), serum hexanoyl lysine (HEL) and peritoneal fluid HEL.Participants/Materials, Setting, and Methods We enrolled 86 women with primary infertility; the case group included 57 women with endometriosis, and the control group included 29 women with unexplained primary infertility. All the patients underwent laparoscopy, and the diagnosis was confirmed histologically. RANDOX and RANSEL reagents were used to determine the levels of SOD and GPX, respectively, and ELISA was used to determine the levels of HEL.Results We found no statistically significant differences in the erythrocyte levels of GPX (p value 0.623) or SOD (p value 0.122) or the serum or peritoneal fluid levels of HEL (p value 0.562 and 0.329 accordingly).Conclusions SOD, GPX, and HEL levels most likely do not differ between patients with unexplained infertility and patients with endometriosis.